A metabolic and genomic study of engineered saccharomyces cerevisiae strains for high glycerol production - Cordier, Hélène (2010)
Towards a global objective to producechemical derivatives by microbial processes, this work dealt with a metabolic engineering of theyeast Saccharomyces cerevisiae for glycerol production. To accomplish this goal, overexpression of GPD1was introduced in a tpi1D mutant defective in triose phosphateisomerase. This strategy alleviated the inositol-less phenotype of this mutant, by reducing the levelsof dihydroxyacetone phosphate and glycerol-3-P, two potent inhibitors of myo-inositol synthase that catalyzes the formation of inositol- 6-phosphate from glucose-6-phosphate. Further deletion of ADH1 and overexpression of ALD3, encoding, respectively, the major NAD+-dependent alcohol dehydrogenase and a cytosolic NAD+-dependent aldehydedehydrogenase yielded a yeast strain able toproduce 0.46 g glycerol (g glucose) 1 at a maximal rate of 3.1 mmol (g dry mass) 1 h 1 in aerated batch cultures. At themetabolic level, this genetic strategy shifted the flux control coefficient of the pathway to the level of the glycerol efflux, with aconsequent intracellularaccumulation of glycerol that could be partially reduced by the overproduction of glycerol exporter encoded by FPS1. At thetranscriptomic level, this metabolic reprogramming brought about the upregulation of genes encodingNAD+/NADP+ bindingproteins, a partial derepression of genes coding for TCA cycle and respiratory enzymes, and a downregulation of genes implicated inprotein biosynthesis and ribosome biogenesis. Altogether, these metabolic and molecular alterations stand for major hurdles that mayrepresent potential targets for further optimizing glycerol production in yeast.